Analyzing Mobile Banking User Experience Using the Modified HEART Metrics Framework - Miftah Rahmaddani; Anita Wulansari; Rafika Rahmawati (Komunitas Dosen Indonesia, 2025)
The rapid development of mobile banking services in Indonesia has facilitated digital financial transactions for the public. BLU by BCA Digital, a fully branchless banking innovation, has experienced significant user growth, yet continues to receive complaints regarding technical issues and unintuitive features raising concerns about the quality of its user experience (UX). This study analyzes the UX of the BLU application using a modified HEART Metrics framework, which includes five dimensions Happiness, Engagement, Adoption, Retention, and Task Success and incorporates an additional variable, Intention to Reuse, to better capture long-term user behavior. The integration of this variable, grounded in the Theory of Planned Behavior, enhances the framework by linking user satisfaction with behavioral intention. Data were collected from 476 active users through an online survey and analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) method via SmartPLS 4. The results show that Happiness, Engagement, Adoption, and Task Success have a significant positive effect on users’ intention to reuse the application, while Retention does not. This suggests that task efficiency and emotional satisfaction play a more crucial role in sustaining user engagement than habitual usage alone. Additionally, Adoption was rated at the lower threshold of the “Good” category in the Goal-Signal-Metrics (GSM) analysis, indicating a need for better onboarding and first-time user experience. These findings offer theoretical contributions to UX measurement and provide practical insights for developers to enhance mobile banking applications and foster long-term user loyalty.